PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2010 – 2013) (Students' Journal of Accounting and Banking, 2015)
The purpose of this study was to determine the influence investment decisions, financing decisions, dividend policy and the profitability of the firm is value. This research was conducted at the Indonesian Stock Exchange by using go public manufacturing company.The population this studyare155companies listedinIndonesia Stock Exchange in2010-2013. The sampling method used purposive sampling. The amount of sample using 14 companies.Mechanicaltesting ofthe dataisbyusing multiple linearregressionanalysis The result showed that Investment decisions, financing decisions, dividend police and profitabilty significant positive effect to firm value.Keywords: Investment Decisions, Financing Decisions, Dividend Policy, Profitability, Firm Value